2014
DOI: 10.1002/smll.201303876
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Inspired Biophotonic Surfaces with Self‐Antireflection

Abstract: with interstitial medium can be considered as single-layer ARS. Based on the Maxwell Garnett model, [ 5 ] the self-antirefl ection can be realized by using the spontaneous index modulation of ARS, i.e., medium-fi lled GNA with ∼0.5 FF, at both air-substrate ( n air and n sub ) and solution-substrate ( n sol and n sub ) interfaces, where a surrounding medium with an index ranging from 1.0 to 1.8 completely fi lls the interstitial gaps between the nanopillars. As a result, the effective index naturally meets an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…In 2014, Jeong and co‐workers proposed the fabrication of biophotonic surfaces with antireflection features inspired by biological nanoarchitectures ( Figure ) . These antireflective structures were based on the corneal surface of moth eyes, which allows a successful modulation of the effective index via its fill factor (FF), i.e., control of the relative fraction of subwavelength nanostructures leads to the desired antireflective condition at the air–solid interface.…”
Section: Ileds Oleds and Lecs Based On Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Jeong and co‐workers proposed the fabrication of biophotonic surfaces with antireflection features inspired by biological nanoarchitectures ( Figure ) . These antireflective structures were based on the corneal surface of moth eyes, which allows a successful modulation of the effective index via its fill factor (FF), i.e., control of the relative fraction of subwavelength nanostructures leads to the desired antireflective condition at the air–solid interface.…”
Section: Ileds Oleds and Lecs Based On Biological Materialsmentioning
confidence: 99%
“…SEM pictures of biologically inspired surfaces with self‐antireflection for highly sensitive biophotonic sensing and imaging. Reproduced with permission . Copyright 2014, WILEY‐VCH Verlag GmbH & Co. KGaA.…”
Section: Ileds Oleds and Lecs Based On Biological Materialsmentioning
confidence: 99%
“…Localized surface plasmon resonance observed in noble metal nanoparticles has received much attention for the enhancement of surface sensing and biophotonic imaging . Oh et al reported biologically inspired biophotonic surface with self‐antireflection together with the nanoplasmonic surface in Figure a . Unlike typical antireflective structures using the modulation of effective index by tailoring the fill factor, antireflection for diverse surrounding media in different indices can serve as a self‐antireflection.…”
Section: Perspectives and Prospects Using Plasmonics/metamaterials Fomentioning
confidence: 99%
“…Plasmonics and metamaterials with insect smartness for ultrathin, miniaturized nanoscale structures: a) Plasmonic self‐antireflection by employing glass nanopillars on dual sides of a substrate for biological sensing and imaging. Reproduced with permission . Copyright 2014, Wiley‐VCH.…”
Section: Perspectives and Prospects Using Plasmonics/metamaterials Fomentioning
confidence: 99%
“…9,13,29 Self-assembled colloidal nanospheres and anodic porous alumina membrane combined with reactive ion etching (RIE) process have been used for fabricating periodic upright tapered SWS. 38 By tuning the parameter of SWS, to enhance the transmission at the full visible range can be made easily. 19,32,33 Although both sides of quartz substrate can reect visible light, most studies on transmission enhancement are focused on fabricating SWS on one side of the transparent substrate.…”
Section: Introductionmentioning
confidence: 99%